A multistage research on factors influencing and active learning intervention on health literacy of community-residing elderly adults in Nanjing - Shengxuan Jin; Ruobing Fa; Jianqian Chao; Na Zhang; Min Bao; Yanqian Wu; Leixia Wang; Gangrui Tan (BMC Public Health)
Abstract Background The health literacy among older adults deserves further investigation. This study aimed to conduct a multistage research to investigate the current status and key determinants of health literacy among Chinese older adults and evaluate the effectiveness of an active learning intervention in enhancing their health literacy. Methods In the first phase, a cross-sectional study surveyed 608 elderly residents. The second phase was a two-arm parallel randomized controlled trial (RCT) in which 120 older adults were randomly assigned to a three-month intervention (n = 60) or control group (n = 60). The active learning program intervention included health lectures, active discussions, heuristic questioning, and family homework, while the control group only received health literacy pamphlets. Health literacy scores were the primary outcome and were evaluated from five dimensions. The RCT data was collected at baseline and the completion of the intervention. Results In the cross-sectional study, the median (IQR) health literacy score was 4.355 (4.030, 4.647) (range: 0–5) Quantile regression showed that sex, education, number of children, self-reported health, chronic disease and insurance significantly affected health literacy. The intervention group showed significant improvement in all dimensions (P < 0.05), with significant group × time interactions in health knowledge, health behaviours, health skills, health intentions and total health literacy. Multiple linear regression indicated that marriage status related to health knowledge, education level related to health behaviours and total health literacy, chronic diseases and insurance factors related to health skills, and sex and insurance factors related to health intentions have significant effects. Conclusion The health literacy of older adults is influenced by individuals, families, and societal factors. The active learning program effectively enhances comprehensive health literacy and is a valuable strategy for advancing China’s proactive health strategy by mobilizing the roles of the individual, family, and society. Trial registration The trial has been retrospectively registered on April 8, 2025, at the Chinese Clinical Trial Registry (ChiCTR2500100396|| http://www.chictr.org.cn/ ), which is a primary registry of the International Clinical Trial Registry Platform of the World Health Organization.